Perancangan 3D Modeling Kapal dan VFX Water Simulation Dalam Animasi 3D Berjudul "Blue & Flash" - Perdinan R. Simamora; Selly Artaty Zega; Weimpy Ocastian Putr Pratama (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2019)
Modeling is the process of modeling according to the object. Modeling is also called the process of modeling digitally from a tangible form using a special software. In animated videos, good modeling does not quite attract the viewer's attention without visual effect. Visual effects or VFX are computerized processes where images or object models are created and manipulated that involve making digital effects recordings and special effects generated by computers to create a virtual environment. 3D models created and given VFX will provide visual looks that look more real. VFX is commonly used in 3D animation filmmaking especially in fantasy themes. One of the most used VFX is water, including wakes, splashes of water and waterfalls. It is hoped that the making of this research can explain the the creation of VFX that supports environment and character.